Characteristics of a reciprocating pump for low-cost sustainable water hydraulic technology demonstrator - Yusof, Ahmad Anas; Zaili , Zarin Syukri; Mohd Nor, Nur Fathiah; Mohd Hanafi, Mohd Hafidzal (TTP USA, 2015)
An investigation of water-based reciprocating triplex piston pump was conducted to propose a low cost solution for the substitution of the traditional oil hydraulics to water hydraulics. Triplex pumps used in this investigation as the water hydraulics require continuous pumping. These pumps are capable of handling a wide range of fluid types, including corrosive fluids, abrasive fluids, and slurries containing relatively large particulates. Thus, an evaluation of the triplex pump using a simple simulation process that focuses on the volumetric efficiency has been conducted in order to understand its ability in energy-efficient system. In this paper, the results of a simulated study of a positive displacement triplex piston pump are presented. The result concludes that the use of water is relatively efficient if the slip factor is maintained to 0.003, with the system pressure is set from 10 to 40 bar.